SPSS survival manual a step by step guide to data analysis using IBM SPSS - Pallant, Julie (Open University Press, 2013)
The SPSS Survival Manual throws a lifeline to students and researchers grappling with this powerful data analysis software. In her bestselling guide, now covering up to version 21 of the SPSS software, Julie Pallant guides you through the entire research process, helping you choose the right data analysis technique for your project. From the formulation of research questions, to the design of the study and analysis of data, to reporting the results, Julie discusses basic and advanced statistical techniques.She outlines each technique clearly, with step by step procedures for performing the analysis, a detailed guide to interpreting data output and an example of how to present the results in a report. For both beginners and experienced users in psychology, sociology, health sciences, medicine, education, business and related disciplines, the SPSS Survival Manual is an essential text. Illustrated with screen grabs, examples of output and tips, it is supported by a website with sample data and guidelines on report writing. This fifth edition is fully revised and updated to accommodate changes to IBM SPSS version 21 procedures, screens and output. Additionalrecommended readings and websites have been added.